A Critical Look at On Est Ensemble: 852 mots pour comprendre le français du Gabon. - Ondo-Mébiame, Pierre; Ekwa Ebanéga, Guy-Modeste (Lexikos, 2011)
The book On Est Ensemble: 852 mots pour comprendre le français du Gabon (L. Ditougou, 2009) is an important contribution to the history of French spoken in Gabon. However, this work presents some shortcomings from a metalexicographic point of view. These relate to the front matter text, the central list (the macrostructure, the microstructure, the access structure, the addressing structure and the mediostructure) and the back matter text. This article aims to address these shortcomings, and, at the same time, to propose ways that could help improve them.